Determining the cost of acute stroke care for a single stay at a tertiary care centre in Pakistan - Khan, Muhammad Farhan; Rasool, Sundus; Muhammad Ijaz; Muheer Khan; Ahmad, Sohail (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the economic burden of acute stroke, and to determine the average cost of acute stroke care for a single hospital stay in a public tertiary care hospital. Method: The cross-sectional study was conducted at the Medical Teaching Institute, Bacha Khan Medical Complex, Swabi, Pakistan, from May 16 to September 19, 2022, and comprised patients of either gender who were hospitalised with an acute stroke for the first time. All costs incurred during the care of the patients were measured using the micro-costing methodology, and the association of the cost with other variables was evaluated. Data was analysed using SPSS 24. Results: Of the 34 patients, 24(70.6%) were males and 10(29.4%) were females. The overall mean age was 66+/-13.00 years. The mean length of hospital stay was 4+/-3.00 days. The mean total cost was 18,156+/-9,068 Pakistani rupees, which was the equivalent of 76.89+/-38.4 United States dollars. The cost of the first day of admission was the highest, declining per day as the stay progressed, and imaging/laboratory investigations formed the highest component of the overall cost (p<0.001). Conclusion: The cost of acute stroke care was found to be high even in a public hospital. The length of hospital stay was the most important determinant of the overall cost. Key Words: Cost of illness, Healthcare costs, Stroke/economics, Length of stay, Hospitalisation, Economics, Pakistan, Public facility.